W cieniu własnej marki. Historia wrocławskiej firmy M. Kempinski & Co - Nowosielska-Sobel, Joanna; Sobel, Grzegorz (Uniwersytet Wrocławski Wydział Nauk Historycznych i Pedagogicznych. Instytut Historyczny, 2021)
The paper describes the circumstances of establishment and functioning of one of the most renowned wine and gastronomy companies in Germany in the 19th and 20th century – M. Kepinski & Co. Both the research and the paper narrative center on the formational process of the company, which now constitutes a timeless brand in the full meaning of the word, being an umbrella brand for a five-star hotel corporate group M. Kempinski & Co., with the headquarters in Geneva and establishments in Berlin, Munich, Dubai, Singapore, Havana, Riga and Vilnius, among others.
Keywords: regionalizm; region; Śląsk; Polska; Czechy; Niemcy; czasopismo regionalne; czasopismo historyczne